"End of Labour": Myth or Reality of Postindustrialism - МакароваМарина Николаевна (Journal of Economic Sociology, 2010)
More and more western researchers use term “end of labour” in their studies of contemporary socio-economic systems of developed countries. This notion characterizes the tendencies linked with the changes of the labour meaning and reallocation and vanishing of the class industrialism relations. In order to have a detailed analysis of labour process transformation and future of labour we need to consider a list of aspects that are more likely to be changes in the contemporary society. The author of the paper focuses on the meaning, structure and personal characteristics of the labour which reflect aspects of changes.